Information security threats and an easy-to-implement attack detection framework for wireless sensor network-based smart grid applications - Tuna, G.; Orenbas, H.; Das, R.; Kogias, D.; Baykara, M.; Gulez, K. (Iop Publishing Ltd, 2016)
Wireless Sensor Networks (WSNs) when combined with various energy harvesting solutions managing to prolong the overall lifetime of the system and enhanced capabilities of the communication protocols used by modern sensor nodes are efficiently used in are efficiently used in Smart Grid (SG), an evolutionary system for the modernization of existing power grids. However, wireless communication technology brings various types of security threats. In this study, firstly the use of WSNs for SG applications is presented. Second, the security related issues and challenges as well as the security threats are presented. In addition, proposed security mechanisms for WSN-based SG applications are discussed. Finally, an easy-to-implement and simple attack detection framework to prevent attacks directed to sink and gateway nodes with web interfaces is proposed and its efficiency is proved using a case study.
5th International Conference on Materials and Applications for Sensors and Transducers (IC-MAST) -- SEP 27-30, 2015 -- Mykonos, GREECE
Keywords: Communication Technologies